Spectral, electrochemical and anti-microbial studies of nicotinic acid hydrazide Schiff base complexes of cobalt (II) and manganese (II) - M.A, Hapipah; M. Zain, Sharifuddin; Jefrey B, Wan; S.M, Rahuma; Rohaiza S.O, Sharifah; Abdullah, Noorlidah; H.L, Teoh (Malaysian Journal of Science, 2004)
A series of Schiff base cobalt(II) and manganese(II) complexes of aroyl hydrazone derivatives of 2-hydroxyacetophenone, 5-chloro-2-hydroxyacetophenone and 2,4-dihydroxybenzaldehyde with nicotinic acid hydrazide have been synthesized. The new complexes have been characterized by elemental analyses, spectral studies, conductivity and magnetic studies, redox studies, thermal analyses and biological activity. The spectral studies suggested that the complexes are coordinated through the carbonyl oxygen and the azomethine nitrogen of the Schiff base. On the other hand, the dihydroxybenzaldehyde Schiff base has been shown to bind to the metal as a tridentate ligand via the ONO coordination sites. The redox properties of the complexes have been investigated by cyclic voltammetry. The difference between the cathodic and anodic peaks, ÃŽâ€E, in the investigated complexes is more than 59 mV indicates that there is only one electron transfer in the oxidation process of the metal. The thermal studies indicated the presence of coordinated water in the 2-hydroxyacetophenone Schiff base complex structure. The anti-microbial studies showed that there was growth inhibition exhibited by some complexes against various gram-positive and gram-negative bacteria tested.